Management of Botrytis Gray Mold (Botrytis cinerea Pers. Ex. Fr.) of Chickpea at Tarahara, Nepal - Chaurasia, Prem CP; Joshi, Sharada (Nepal Agriculture Research Journal, 2011)
An experiment was conducted in randomized complete block design with six treatments and four replications at loamy soil of Regional Agriculture Research Station, Tarahara, Nepal during 1997/98 and1998/99 seasons to find out the effect of bioagent Trichoderma viride as compared to fungicide Bavistin (carbendazim) for management of Botrytis gray mold (Botrytis cinerea) of chickpea (Cicer arietinum). Treatments were use of water spray (check), three sprays of T. viride (107-108 spores/ml of water), three sprays of Bavistin @ 0.2%, three sprays of Bavistin @ 0.1% + T. viride, two sprays of Bavistin @ 0.2% and two sprays of T. viride. The area under the disease progress curve (AUDPC) was the least (193.6) with three sprays of Bavistin (0.2%) followed by two sprays of Bavistin (0.2%) and three sprays of Bavistin + T. viride (216.9). The highest mean grain yield of 267.3 kg ha-1 was produced by three sprays of Bavistin + T. viride followed by three sprays of Bavistin. Three sprays of T. viride was inferior to three and two sprays of Bavistin but it was at par with two sprays of T. viride with respect to grain yield production and reduction of Botrytis gray mold severity. When AUDPC was regressed against grain yield, a negative correlation was obtained between the disease and the grain yield. The correlation coefficients for the disease and yields during 1997/98 and 1998/99 respectively were -0.583, and -0.490. Key words: Botrytis gray mold; Chickpea; Trichoderma DOI: http://dx.doi.org/10.3126/narj.v4i0.4867 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 37-41 Uploaded date: 9 June, 2011